Economic Warfare in the 21st Century
IX, 238 p. 13 illus., 12 illus. in color.
Keywords: This volume critically examines whether the United Kingdom, NATO, and the EU are equipped to engage in both defensive and offensive economic warfare. In an era where economic leverage is increasingly used as a tool of statecraft, nations worldwide are struggling with the complexities of economic warfare. The book discusses contested terminology and concepts, often blurred with geoeconomics, economic statecraft, and weaponized interdependence. Through a thorough analysis of organizational structures, doctrines, and strategic cultures, the book explores the legitimacy and implications of using economic means to influence state behavior. As global actors ramp up their economic warfare capabilities, it questions whether such strategies are a necessary evolution or a disruptive force to international norms. The book will appeal to students, researchers, and scholars of international relations, political science, security studies, and defence studies, as well as policy-makers and practitioners interested in a better understanding of the future of global economic security.